PERILAKU MAKAN GAJAH SUMATERA (Elephas maximus sumatranus) DI PUSAT KONSERVASI GAJAH TAMAN NASIONAL WAY KAMBAS - Riba'i .; Agus Setiawan; Arief Darmawan (Media Konservasi, 2013)
This research was purposed to find out the Sumateranus elephants natural eating behavior and to find out the level of it favorite woof (palatabilitas) by used exploration method.  The result of the research shows that adult male and female of Sumateranus elephant have the same natural eating behaviour.  The natural eating bahaviour is divided into 3 division based on the shepherding place, the are savannah, swamp, and secondary forest.  Such kinds of natural woof that are consumed by elephant:  ilalang (Imperata cylindrical), rumput gajah mini (Elytrigia repens), putri malu (Mimosa pudica), rumput teki (Cyperus rotundus), jambu biji (Psidium guajava), benalu belimbing (Macrosolen cochinchinensis), kalopogonium (Calopogonium mucunoides), polongan (Pueraria phaseoloides), rumput bambu (Digitaria ciliaris), paku merak (Selaginella willdenovii), sawi langit (Vernonia cinerea), grintingan (Cynodon dactylon), paku hata (Lygodium circinatum), senggani (Melastoma polyanthum), teki rawa (Cyperus alternifolius), mendong (Cyperus compressus), lingi (Typha latifolia), suket godokan (Fimbristylis ferruginea), teratai (Nymphaea alba), palem serdang (Livistona rotundifolia), jabon (Anthocephalus cadamba), rotan duduk (Daemonorops longipes), sungkai (Peronema canescens), and sonokeling (Dalbergia latifolia).  Eating frequency is influenced by 3 factors they are the availability of woof, condition of health, and weather.  The longest eating duration find in secondary forest.  The are 5 division of part of woof that is consumed trunk, skin, leaves, and fruits.  The way of eating is by cleaning the woof first by swaying it by using its snout.  Its most favorite woof are:  rumput gajah mini, teki rawa, ilalang, and palem serdang. Keywords: Feeding behaviour, sumateranus elephant, Elephant Conservation Center.